Genitourinary diseases prior spontaneous abortion as a risk factor for recurrent pregnancy loss - Čulić, Vida; Konjevoda, Paško; Miše, Kornelija; Kardum, Goran; Matijević Glavan, Tanja; Pavelić, Jasminka (2009)
Abstract: The etiology of recurrent spontaneous abortion (RSA) is still unexplained. Many couples do not find the cause of their RSA at all. The purpose of this research was to evaluate the association between recurrent pregnancy loss and previous (cured prior to pregnancy) acute/chronic genitourinary infections in both parents. Couples (226) having two or more (up to six) spontaneous abortions were analyzed in this retrospective case-control study. The control group consisted of 124 couples with neither miscarriages nor complicated pregnancies in their past. The data (serum immunological markers, karyotype, flow cytometry data, PHD) were collected from their medical charts. It was found that there was no statistically significant difference in average weeks of pregnancy in which the second, third and fourth abortion occurred. There was a statistically significant difference in previously experienced genitourinary infections between women from the RSA group and the control group, as well as for men from the RSA group and the control group. It can be concluded that past infections of the maternal and/or paternal genitourinary system may be the causal factor for recurrent pregnancy loss and can also pre-determine women that are of greater susceptibility to preterm pregnancy. Therefore the genetic counseling of couples should include thorough medical and family history of both partners and their first- and second-degree relatives in conjunction with typical medical examination
Bibliografija: 48 jed
Sažetak
Keywords: Spontani opetovani pobačaji -- Genitourinarne bolesti -- Rizični čimbenici